61.2k views
5 votes
Is 11-2x the same as 2x-11

User Buba
by
5.4k points

2 Answers

5 votes

No they are not the same.

We can plug in x = 0 to get

11-2x = 11-2(0) = 11-0 = 11

2x-11 = 2(0)-11 = 0-11 = -11

We get the results 11 and -11 for the expressions 11-2x and 2x-11 respectively. Since we got different outputs, this is enough to show that the expressions are not the same. They would need to produce the same outputs for any given x value.

On a graph, y = 11-2x and y = 2x-11 are two different lines to show they are not the same expression.

note: if you plug in x = 11/2 = 5.5, then both outputs are the same; otherwise, you'll get different outputs.

User Ahodder
by
5.5k points
6 votes
No, they aren’t the same.

For example, if x equaled 3
11-2(3) = 5
2(3)-11 = -5
User Tomak
by
5.9k points